Comparing the coarse- and high-resolution horizontal and vertical egg distribution patterns of three clupeiform species in the southern Benguela ecosystem - Dopolo, Mbulelo Tomie (Department of Biological Sciences, 2014)
Bibliography: leaves 122-159.